PRAKTIK PERSONAL HYGIENE MENSTRUASI PADA REMAJA PEREMPUAN DI SMP NEGERI 4 BANJARANGKAN - Ningrum, Ida Ayu Siwi Kalfika; Yuli Kurniati, Desak Putu (ARCHIVE OF COMMUNITY HEALTH; Vol 11 No 3 (2024): Desember 2024DO - 10.24843/ACH.2024.v11.i03.p17, 2025)
Menstruation is a significant milestone indicating a girl's entry into adolescence. During menstruation, the risk of infection in the blood vessels of the uterus is heightened. These infections can be caused by microorganisms, resulting in itching, irritation, or abnormal discharge.. Based on previous interviews, it was found that many adolescent girls have experienced itching in the genital area. Therefore, practicing personal hygiene during menstruation becomes crucial to prevent diseases. The aim of this research is to investigate the menstrual personal hygiene practices among female adolescents at SMP Negeri 4 Banjarangkan. The research adopts a qualitative research method using purposive sampling technique. The total number of informants is 21, divided into 3 focus group discussions with a total of 18 participants and 3 individual interviews. Thematic analysis is employed to analyze the data. The findings reveal that the knowledge, attitudes, perceptions, and practices of menstrual personal hygiene among adolescent girls are not adequately performed. Additionally, the availability of facilities, resources, and information poses challenges for female adolescents in fulfilling menstrual personal hygiene practices, particularly within the school environment. Despite these challenges, adolescent girls receive instrumental and informational support from parents, friends, teachers, and healthcare providers in meeting their menstrual hygiene needs. Keywords: Menstrual Hygiene, Adolescents, School, Klungkung